The effectiveness of web-based grammar instruction and students' attitude towards learning basic English grammar / Rafidah Abd Karim - Abd Karim, Rafidah (Division of Research, Industrial Linkages and Alumni, UiTM Cawangan Melaka, 2011)
Language teachers and learners now have various learning Websites with interactive contents that offer certain advantages over conventional teaching instructions. Therefore, the aim of the study is to compare the two teaching methods; Web-based Instruction (WBI) versus Conventional Textbook Instruction (CTI) on Diploma students in a branch campus of a public university in Malaysia. This study also determined the students’ attitude towards learning of basic English grammar by using the Web-based Instruction approach in the classroom. The quasi experimental research and survey design were utilized to carry out this study. The participants in this study were 60 Diploma students of two classes in the university. The T-test result showed that the students for experimental group who went through WBI performed better than those who use CTI in learning basic grammar items. The results of the questionnaire also showed that the students generally had positive attitudes toward the use of Web-based Instruction iii learning basic English grammar. Finally, the study concluded that there was a statistically significant relationship between the students’ attitude toward the use of Web and their grammar skill performance. Results of these findings suggest that the WBI is a practical instrument in learning basic English grammar.